(3CWQGa GdUMjMjfs - (3Nda Hf eMeO Hf Ydj Hf MeOhf GdhGSWj, CHh eMeO,J (B401 (3g` s
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HMOjK (B: (3Gfg JhVC aZSd hLgI s
(3GdfSNI HgG MhGTs
(3jHJOF HGdLRA GdChd hjfJgi HGdLRA GdMGOi YTQ ef JLRFI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B311 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B107s
Keywords: (3GdMOjK h GdeUWdMs